Emergency laparoscopic resection of the anterior rectum due to rectal trauma secondary to compressed air, case report (2020)
In the XIX century, the surgeon faces surgical challenges due to the creation of new technologies. Accidental or compressed air-induced injury to the colon and rectum is rare. We present the case of a 45-year-old patient who consults the emergency department, then a high-pressure rectal pneumatic trauma, with clinical findings of peritonism, managed with a Hartmann-type colostomy. and anterior resection of the rectum using laparoscopy, with findings of rectosigmoid perforation. With this, it can be demonstrated that minimally invasive surgery is a feasible approach in hemodynamically unstable patients without contraindication for pneumoperitoneum.